Patients' Experiences of Deciding Whether or Not to Accept Bone Conduction Hearing Implants: A Qualitative Investigation. Issue 2 (24th March 2021) - McFarland, Sophie M.; Powell, Rachael; Green, Kevin; Andrew, Rachel; Coppack, Kathryn; Hill-Feltham, Penny; Wearden, Alison
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Bone conduction hearing implants (BCHIs) are an effective option to rehabilitate hearing for people who cannot use conventional, air conduction hearing aids. However, the uptake of such devices in the United Kingdom is lower than might be expected, and the reasons for this are not fully understood. The present study used qualitative methods to explore decision-making about whether to accept or reject BCHIs. Design: Semistructured telephone interviews were conducted with 17 BCHI candidates who had recently accepted or rejected BCHIs. Results: A thematic analysis identified four overarching themes: participants wanted to look and feel normal; potential risks were weighed against rewards; participants felt that there was a "right time" to have a BCHI; and information from clinicians and BCHI users was treated differently. Participants' perceptions of normality were influential in the final decision, and the BHCI was seen either as a barrier or facilitator of this. Participants consistently weighed up potential advantages and disadvantages of BCHIs, with potential for hearing improvement typically used as a benchmark against which other factors were measured. Some participants who rejected BCHIs felt that they could reconsider having a BCHI when they felt the time was right for them. Participants highly valued advice from clinicians, but felt that their expertise lacked validity as clinicians typically did not have experience of using BCHIs themselves. Conclusions: The decision to accept or reject a BCHI was highly individual. Each participant considered a range of factors; the influence of each factor depended on the individual's perceptions and experiences. This work highlights the importance of clinical staff being able to explore the individual priorities and concerns of each patient to ensure that patients feel happy and confident with the decision that they make.